MĘSKI „DEFICYT” I „KOBIECA TWARZ ROSJI” - Pogonowska, Ewa (Przegląd Rusycystyczny, 2016)
Мужской «дефицит» и «женское лицо России» Статья посвящена восприятию женщины и её отношениям с мужчиной в польских репортажных рассказах о России. автор статьи особенно заинтересовалась пробле-мой восприятия статуса русской женщины в преобразованном и наученным но-вым историческим опытом обществе. Привилегирование мужского пола уже на уровне семейной социализации и зависимость сыновей от матери отражается в девальвации идеи мужчины — кормильца семьи. В современной России именно женщина берет на себя роль «сильного пола», более умело справляется с вызовами времени и маргинализирует слабого автодеструктивного мужчину. The “deficit of man” and “the feminine face of Russia” The paper is about the perception of woman and her relationships with man in Polish reportage narratives about Russia. The author’s main interest is the status of Russian women which undergoes various transformations, part of which are the historical expe-riences of the society. Both the preferences and privileges for men on the level of family socialization and their strong dependence on their own mothers contributes to devalu-ation of traditional idea of a man, who supports his family. In modern Russia it is the woman who serves as “the stronger sex” and deals with the challenges of everyday life better than the man — weaker, self-destructive and more and more marginalized.